Modeling of local damage in automobile internal combustion engines - Kravchenko, Oleksandr; Khrulev, Alexander; Gerlici, Juraj; Saraiev, Oleksii (Žilinská univerzita v Žiline : EDIS-vydavateľstvo UNIZA, 2025)
The monograph examines a number of hitherto unnoticed and insufficiently studied mechanisms of failure that cause local operational damage in automobile internal combustion engines. The general concept of modeling processes and mechanisms of the origin and development of engine failures is presented. The task, possibilities, purpose and features of mathematical modeling of processes that lead to damage and failure of engines are determined. The difference between modeling of operational engine damage and modeling during design and research work is shown. The main processes of local damage work is shown. The main processes of local damage in engines are considered, mathematical models of the considered processes are described in detail, and the results of modeling on examples of specific structures are presented. Based on the research results, it was concluded that the developed models can be used in practice in identifying the causes of engine failures of various types, and their use in professional studies can increase the accuracy and objectivity of expert opinions. The book is intended for undergraduate, graduate and postgraduate students, as well as researchers in the field of Automotive Operation, but may also be useful for engineers, professionals and scientists in other fields related to process reseaarch, design and operation of internal combustion engines